ANALYSIS OF TIME ACCELERATION OF THE XYZ BUILDING PROJECT - Sugeng Santoso; Ester Melina; Priskila Dorothy; Unggul Wahyu Aji (SEAN Institute, 2022)
Contract time that has been decided in the beginning is the time for contractors to start and finish the project. But if the contractor should finish the project early from the contract, it should be accelerated. The consequence of accelerating will increase cost, caused by increased working time or manpower. The purpose of this research is to know the increasing cost amount after accelerating the project XYZ building. Quantitative descriptive is used in this study, with critical path & MS Project method. The result of this research is to count the additional cost after acceleration as 3 times more than begging. We can conclude that acceleration will increase more cost. We suggest the contractor ask for additional costs from the owner, so the project acceleration can be done in time.